REPRESENTASI KEKUASAAN BAHASA DALAM PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH PERHOTELAN BALI - Ida Ayu Gayatri Kesumayathi (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The success of English language learning depends on various factor. One of them is communication between teacher and students which can be seen from the language they used. The study aims at finding the representation of power in teacher speech acts during teaching and learning process in the classroom. The study is a qualitative research involving two teachers who taught English language. The obtained data were collected through observation and video recordings. The data were analysed based on speech acts theory proposed by Searle and theory of power by French and Raven. The study found there were representation of power such as legitimate power, expert power, and reward power in teachers’ speech acts such as representative, directive, commissive, and expressive during English language learning in Sekolah Perhotelan Bali.